Preparation of albumin nanospheres loaded with gemcitabine and their cytotoxicity against BXPC-3 cells in vitro - Li Jin-ming; Chen Wei; Wang Hao; Jin Chen; Yu Xian-jun; Lu Wei-yue; Cui Long; Fu De-liang; Ni Quan-xing; Hou Hui-min (Acta Pharmacologica Sinica, 2016)
Aim: To optimize formulation methods for loading gemcitabine (GEM), the main drug against pancreatic cancer, into albumin nanoparticles for extended blood circulation and improved efficacy. Methods: GEM was loaded into two sizes of disolvation-crosslinked bovine serum albumin nanoparticles, with a mean diameter of 109.7 nm and 405.6 nm, respectively, by co-precipitation (the direct method) and follow-up adsorption (the indirect method). The antitumor activities of the two nanoparticulate formulations, were evaluated according to their anti-proliferative effects on the human pancreatic cell line BXPC-3, which were assessed using the MTT assay. Results: The two nanoparticulate formulations, created by direct co-precipitation and indirect adsorption, possessed smooth surfaces and high drug loading efficiencies, 83% and 93% at 11% and 13% drug loading, respectively. The two formulations released GEM for 8 and 12 h, respectively, and significantly improved anti-BXPC-3 proliferation effects, as compared with the GEM solution and the drug-free albumin particles. Conclusion: Co-precipitating and adsorbing GEM into albumin particles resulted in sustained-release nanoparticulate formulations with improved antitumor cytotoxicity. The result suggests that this is a useful formulation strategy for improving the antitumor efficacy of GEM.